Knowledge and Practice of Preventive Measures for Nosocomial Infections among Health Workers in Primary Health Care Center in Aluu, Rivers State - Maynard, Aminaho Ehianu (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2019)
This study examined the knowledge and practice of preventive measures for nosocomial infection among health workers in Primary Health Center in Aluu, Rivers State. A descriptive survey design was used for the study. The population consisted of all health workers at the primary health center during the period of this study. The researcher sampled 52 subjects for data collection. All the workers were included in the study except those on annual leave. Thus the total sampling technique was employed this study. A self-structured questionnaire titled “Knowledge and Practice of Preventive Measures for Nosocomial Infection Questionnaire (KPPMNIQ)” was the instrument for data collection. The validated questionnaire with a reliability index of 0.86 was administered on the respondents by direct delivery method over a period of one week. Only 48 health workers were accessible at the time of conducting the study as the other 4 health workers were on annual leave. Analysis of data was done using the Statistical Package for Social Sciences Software (SPSS) version 22. Results revealed that out of the 48 respondents studied, 4.20% had poor knowledge, 8.30% had fair knowledge while 87.5% had good knowledge of the preventive measures for nosocomial infection; 33.3% practice while 66.7% do not practice preventive measures for nosocomial infection; the challenges of health workers in prevention of nosocomial infection include inadequate equipments such as hand washing sink, the perception that nosocomial infection cannot be completely eradicated, poor health workers’ staffing and bad effects of hand hygiene agents on the skin; Hypothesis test showed that no significant relationship between awareness and practice of preventive measures for nosocomial infection among health workers in Primary Health Center, Aluu. There is therefore the need for hospital policies that will monitor the practice of preventive measures for nosocomial infection among health workers which will go a long way in compelling health workers to practice nosocomial infection prevention thus reducing the incidence of nosocomial infection, it morbidity as well as associated mortality.